Deciphering TCOF1 mutations in Chinese Treacher Collins syndrome patients: insights into pathogenesis and transcriptional disruption - Zhuoyuan Jiang; Ke Mao; Bingqing Wang; Hao Zhu; Jiqiang Liu; Ruirui Lang; Baichuan Xiao; Hailin Shan; Qi Chen; Ying Li; Shouqin Zhao; Qingguo Zhang; et al. (Orphanet Journal of Rare Diseases, 2025)
Abstract Background Treacher Collins syndrome (TCS, MIM #154500), a severe congenital disorder, predominantly involves dysplasia of craniofacial bones and is characterized by features such as downslanting palpebral fissures, lower eyelid colobomas, microtia, and other craniofacial anomalies. Despite its clinical importance, the underlying pathogenic mutations in TCS remain largely uncharacterized, representing a critical knowledge gap for researchers in the field. Results To address this, we performed mutation screening on a familial TCS case (trio) and 11 sporadic cases from a Chinese population. We identified 11 mutations predominantly localized to the central repeat domain (CRD) and the C-terminal domain (CTD, including the nuclear localization sequence) of TCOF1. The de novo frameshift mutation identified in the trio led to TCOF1 truncation, disrupting the central repeat domain crucial for binding transcriptional factors. Immunoprecipitation assays revealed that this pathogenic mutation attenuates the interaction between TCOF1 and transcription-related proteins, such as Pol II. Furthermore, cellular luciferase assays demonstrated that the mutation compromises the nuclear localization capability of TCOF1. Conclusions Our findings establish TCOF1 as the primary pathogenic gene in this Chinese TCS cohort, with mutations predominantly in the CRD and CTD, thereby expanding the known mutation spectrum of TCS and informing its prevention strategies.